2023
DOI: 10.1155/2023/6655628
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperament on the Acceptance of Two Conscious Sedation Techniques in Toddlers Undergoing Dental Treatment: A Randomised Cross Over Trial

Palak Janiani,
Deepa Gurunathan,
Sivakumar Nuvvula

Abstract: Background. Pediatric dentists often find it challenging to handle pediatric patients due to their fear, unease, and anxiety toward dental procedures. To address this, sedation agents such as intranasal midazolam and nitrous oxide are commonly used as pharmacological behavior management methods. A child’s temperament affects their behavior in unfamiliar settings. Aim. To study the effect of child temperament on the acceptance of the nasal mask and intranasal drug administration in children undergoing dental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The levels of SC and SAA were examined before and after extraction in the saliva samples of 20 children, and it was found that the levels of cortisol and alpha-amylase increased significantly after extraction. There are various studies [15][16][17][18][19][20][21][22][23][24][25] focused on distraction in pediatric clinical settings and this is the first of its kind study involving the evaluation of salivary cortisol levels among children. This is consistent with our study in which salivary cortisol levels were decreased by audiovisual distraction and the use of the WAND injection system, demonstrating their effectiveness in reducing dental anxiety in children [14] .…”
Section: Comparative Analysis Of Effectiveness Ofmentioning
confidence: 99%
“…The levels of SC and SAA were examined before and after extraction in the saliva samples of 20 children, and it was found that the levels of cortisol and alpha-amylase increased significantly after extraction. There are various studies [15][16][17][18][19][20][21][22][23][24][25] focused on distraction in pediatric clinical settings and this is the first of its kind study involving the evaluation of salivary cortisol levels among children. This is consistent with our study in which salivary cortisol levels were decreased by audiovisual distraction and the use of the WAND injection system, demonstrating their effectiveness in reducing dental anxiety in children [14] .…”
Section: Comparative Analysis Of Effectiveness Ofmentioning
confidence: 99%